2019
DOI: 10.2337/dc19-0497
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association Among Diabetes Diagnosis, HbA1c, Glycemia, and Frailty Trajectories in an Elderly Population

Abstract: Frailty is a dynamic state of vulnerability in the elderly. We examined whether individuals with overt diabetes or higher levels of HbA 1c or fasting plasma glucose (FG) experience different frailty trajectories with aging. RESEARCH DESIGN AND METHODS Diabetes, HbA 1c , and FG were assessed at baseline, and frailty status was evaluated with a 36-item frailty index every 2 years during a 10-year follow-up among participants from the English Longitudinal Study of Ageing (ELSA). Mixed-effects models with age as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 36 publications
2
40
0
2
Order By: Relevance
“…Furthermore, we do not know in which component (bone, fat, muscle) the weight loss is occurring when we consider weight change. Loss of muscle mass and bone mass are components of frailty, and people with diabetes experience more frailty with ageing compared with the general population 6 . Our finding of less marked effects in analyses focused on waist circumference compared with weight support that weight loss in the cohort may have occurred in the non‐fat components.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, we do not know in which component (bone, fat, muscle) the weight loss is occurring when we consider weight change. Loss of muscle mass and bone mass are components of frailty, and people with diabetes experience more frailty with ageing compared with the general population 6 . Our finding of less marked effects in analyses focused on waist circumference compared with weight support that weight loss in the cohort may have occurred in the non‐fat components.…”
Section: Discussionmentioning
confidence: 56%
“…15 Three (3%) of 118 studies used both the frailty index and frailty phenotype. [16][17][18] In each of these studies, the percentage of people identified as frail was higher using the frailty index (53%, 30%, and 32%) [16][17][18] compared to using the frailty phenotype (23%, 26%, and 24%), [16][17][18] highlighting the sensitivity of frailty prevalence to the measure used. Frailty prevalence was also notably high in some ethnic groups (eg, African Americans and Aboriginal Australians) and lower in others (eg, Mexican Americans).…”
Section: Resultsmentioning
confidence: 94%
“…Heterogeneity between study estimates was low (I²=0%) despite variation in the length of follow-up and the variables in each model. The only study 16 assessing the association between HbA 1c and changes in frailty status showed that a higher HbA 1c at baseline was associated with worsening frailty over a 10-year period measured using the frailty index. Three studies (3%) of 118 assessed transitions between frailty phenotype states and found that people with diabetes were less likely to improve from a frail to a pre-frail or robust state compared to people without diabetes.…”
Section: Frail Scalementioning
confidence: 99%
“…[11][12][13][14] Thus, the prevention of disability and frailty conditions is important because these conditions severely reduce the quality of life of individuals and are economically burdening for public health. [15][16][17][18] Diabetes per se was reported to be associated with a marked increase in the risks of physical disability and frailty. 15 16 It is also known that a decrease in muscle strength is accelerated by aging, especially in people with diabetes compared with those without diabetes.…”
Section: Introductionmentioning
confidence: 99%